Hopelessness learned in life chain sentences - ESPINOZA YONG, Nelson Pacífico (2021)
The present investigation aimed to identify the levels of hopelessness learned in those sentenced to life imprisonment. It was evaluated using the "Beck hopelessness scale" taking into account the factors: affective, cognitive and volitional. The research had a non-experimental, descriptive, cross-sectional design, made up of a census population of 64 inmates sentenced to life imprisonment in Chiclayo. The results projected the level of affectation of the inmates by showing that they present a severe level between 35.94% and 45.31% of learned hopelessness in its three factors, in turn, the age group that predominates is that of 46 to 60 years, showing that part of those evaluated think that they will not be able to defend themselves and lose hope considering their life sentence by a legal body.Keywords: Learned hopelessness, life imprisonment, affective, cognitive, volitional.